Testing the Link between Accessible Export Finance and Insurance, and Regional Trade Growth in Africa and Asia: A Role for Regional Export Credit and Investment Guarantee Agency (ECIGA) - Hans-Peter Brunner (Asian Development Bank (ADB), 2015)
Using panel data regressions, this paper analyzes the effect of imperfections in the formal export credit and insurance market on trade growth in the regions of Africa and Asia. An exclusive comparison of trade performance of the two regions with respect to export credit and insurance is novel in the literature. I employ Berne Union data on export credit insurance for the period 2005 to quarter 1 (Q1) 2012, which is the most extensive dataset of its kind at the moment. As further novelty, I extend the data specification of Auboin and Engemann (2014) to the interaction of export diversification and complexity, intermediated by an agency variable representing the existence of insurance institutions (Export Credit and Investment Guarantee Agency, or ECIGA), with trade growth, and export credit and insurance. The paper can identify a significantly positive effect from the reinforcing interaction of the export credit and insurance market, and export diversity-complexity on trade.
hdl:11540/4396
Keywords: F13; F36; G14; O16; 330; export finance; product market diversification; regional trade growth